SODY SALLERATUS (Author: Aubrey Davis; Illustrators: Alan & Lea Daniel) - Benson, Fiona; Vourdousis, Dina Vourdousis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1997)
AUBREY DAVIS, ALAN & LEA DANIEL, Illustrators. Sody Salleratus. Toronto: Kids Can Press (1997). Ages 3 - 7. 32 pp. $14.95 (HC); $5.95 (paper). ISBN 1-55074-224-8 & 1-55074-326-0.